THE MANAGEMENT OF CHANGE IN PUBLIC ORGANIZATIONS: A LITERATURE REVIEW - KUIPERS, BEN S.; HIGGS, MALCOLM; KICKERT, WALTER; TUMMERS, LARS; GRANDIA, JOLIEN; VAN DER VOET, JORIS (Public administration (London), 2014)
This article presents a review of the recent literature on change management in public organizations and sets out to explore the extent to which this literature has responded to earlier critiques regarding the lack of (public) contextual factors. The review includes 133 articles published on this topic in the period from 2000 to 2010. The articles are analysed based on the themes of the context, content, process, outcome, and leadership of change. We identified whether the articles referred to different orders of change, as well as their methods and theory employed. Our findings concentrate on the lack of detail on change processes and outcomes and the gap between the common theories used to study change. We propose an agenda for the study of change management in public organizations that focuses on its complex nature by building theoretical bridges and performing more in‐depth empirical and comparative studies on change processes.